Finite element analysis of axial, radial and halbach permanent magnet linear generators - Wijono, S.; Arof, Hamzah; Mahadi, W.N.L.W.; Said, S.M. (Praise Worthy Prize, 2010)
This paper presents a finite element analysis of permanent magnet linear generators. The machines can utilize axially magnetized permanent magnets (AMPM) only, radially magnetized permanent magnets (RMPM) only or a combination of both (Halbach) as the field sources. The study includes the analysis of the magnetic flux, flux linkage, induced voltage, cogging force and core-loss in the machines. The results provide comparative performances of tubular linear generators utilizing AMPM, RMPM and Halbach permanent magnet configuration along with the advantages and drawbacks of each type. It is found that the Halbach configuration provides a compromise between the axial and radial configuration, which results in a moderate induced voltage and overcomes the problem of high cogging force experienced in the axial configuration. Copyright (C) 2010 Praise Worthy Prize S.r.l. - All rights reserved.